2001
DOI: 10.1021/jp010456i
|View full text |Cite
|
Sign up to set email alerts
|

Transferability and Physicochemical Interpretation of Canonical Force Fields in Redundant Internal Coordinates:  Pyridazine and 3,6-Dichloropyridazine

Abstract: The behavior of various force fields for pyridazine and 3,6-dichloropyridazine coming from different origins (i.e., HF/6-31G*, MP2/6-311G**, BLYP/6-31G*, B3LYP/6-31G* previously scaled) and empirical force fields transferred from the benzene molecule is investigated. These potentials are subjected to a linear least-squares refinement with the available experimental information considered as observed data. Moreover, the transferability properties of the force fields for these related molecules are analyzed. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Several papers have recently discussed the canonical force field. 3,4 One of the main advantages of such a force field is that the corresponding force constants are unambiguous, thus providing a very suitable method for making meaningful comparisons between force constants obtained through different systems.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have recently discussed the canonical force field. 3,4 One of the main advantages of such a force field is that the corresponding force constants are unambiguous, thus providing a very suitable method for making meaningful comparisons between force constants obtained through different systems.…”
Section: Introductionmentioning
confidence: 99%
“…This vibrational energy part e CH (θ) is calculated using nine internal curvilinear coordinates of the methyl group, namely the displacement coordinates of the three CH/CD bonds ( r ), of the three HCH/HCD angles and of the three HCC/DCC angles deformations (α). As previously stated, this set of internal coordinates offers a powerful tool to test the physicochemical meaning of the force constants. They also allow transferrability and interpolation of the force fields between related molecules.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…This matter has been treated in the literature from different points of view. The transferability of the canonical force constants has been studied in a wide variety of molecules [19][20][21][22][23] and it has been shown that the canonical force fields are transferable between molecules with the same geometry [17]. The work described here concerns an approach to obtain transferable force fields in terms of redundant and independent symmetry coordinates for molecules with a common group of atoms.…”
Section: Introductionmentioning
confidence: 99%